2 - Community Development: A Cross-Examination of Theory and Practice Using Experiences in Rural Malawi - Jimu, Ignasio Malizani (Africa Development, 2021)
The philosophy of ‘community development’ relates to the concept of ‘locality’ and people. In essence it underscores the indispensability of local needs, aspirations and local resource mobilization within geographically and socially defined spheres. Through an appraisal of community involvement in various projects, this paper interrogates the virtues of community development practices in Malawi in the last 40 years. While acknowledging that community development or local participation, as it is popularly known, is ideal in many development activities, this paper argues that participation is not a magic pill for rural development. Participation in gravity water and social action fund projects, among others, provide instances for appreciating the opportunities and the challenges of community development. One such challenge is the absence of projects that are in every sense community-driven. With few exceptions, there is no participation that is truly voluntary. Vulnerability to poverty and lack of resources at community levels defeat efforts towards genuine community development. This is a similar outcome to projects implemented under coercive rule.